DETERMINATION OF ASSORTMENT STRUCTURE DURING PLANNING THE BREAK EVEN IN WOODWORKING ENTERPRISES (Innovation in Woodworking Industry and Engineering design, 2026)
Problems about production capacity and assortment decision are of the most important for enterprises. They answer the questions for who, what and how to produce. They limit eco-nomic efficiency. Summarize and develop a methodic for calculating capacity and optimizing the structure of assortment would be very helpful for enterprises in the wood processing industry.